Preparation and characterization of molecularly imprinted polymer for melamine - Ab Rahman, Siti Khadijah (2013)
Molecularly imprinted polymers (MIPs) are synthetic polymers having a predetermined selectivity for a given analyte, or group of structurally related compounds, that make them ideal materials to be used in separation processes. In this research, MIP was synthesized and used for selective removal of melamine compound. The MIP was prepared using precipitation polymerization method where melamine as template, 9-vinylcarbazole or methacrylic acid as functional monomer, ethylene glycol dimethacrylate (EGDMA) as a crosslinker and benzoyl peroxide (BPO) as initiator in the same phase. The total weight of yield of MIP increased, by increasing the ratio of initiator, monomer and cross-linker and the suitable temperature was chosen for this polymerization process at 60 oC. The best ratio of monomer to crosslinker is 1:8 for methacrylic acid and 1:5 for 9-vinylcarbazole. The synthesized Mel-MIP-9VC and Mel-MIP-MAA were characterized using fourier transform infrared spectroscopy (FTIR), thermal gravimetric analysis (TGA), field scanning electron microscopy (FESEM) and brunauer, emmet teller (BET) for determining the polymerization and imprinting process were occurred successfully.Adsorption process for the determination of melamine using molecular imprinted solid phase extraction (MISPE) method and adsorption capacities of melamine by Mel-MIP-9VC and Mel-MIP-MAA were analysed by using ultra performance liquid chromatography (UPLC). The optimum adsorption capacity is achieved at pH 5.0 for both MIP (Mel-MIP-9VC and Mel-MIP-MAA). The adsorption isotherm data is well defined by the Freundlich model for both MIP with R2 value of Mel-MIP-9VC and Mel-MIP-MAA are 0.980 and 0.896 respectively. The adsorption of melamine can be modeled by pseudo-second order reaction. The percentage removal of melamine increases with increasing dosage of MIP. The selectivity study shows the adsorption capacity of melamine by MIP is higher than NIP. The k’ value for Mel-MIP-9VC and Mel-MIP-MAA of melamine/cyanuric acid is 3.1651 and 1.6070 respectively. The adsorption capacity of melamine in milk sample by Mel-MIP-MAA and Mel-MIP-9VC is higher than NIP-MAA and NIP-9VC.